Produced Water Treatment Technologies: A Review - Cilia Abdelhamid; Abdeldjalil Latrach; Minou Rabiei; Kalyan Venugopal (Energies)
The oil and gas industry’s view of water production, once regarded primarily as a waste stream, has shifted in recent years due to the growing environmental and economic challenges. Industries now recognize the substantial volumes of water produced during production operations and are actively exploring alternative water management strategies. Among these, water treatment stands out as a leading approach, aimed at purifying the water to achieve specific element concentrations suited for targeted applications. The produced water from oil and gas reservoirs is a complex mixture of various organic and inorganic compounds, as well as dissolved and suspended solids. It is considered a highly contaminated waste stream, making effective treatment essential to meet future critical water demand. The physical and chemical properties of the produced water vary depending on the extraction location, geological formations, and type of hydrocarbon produced. This review examines multiple treatment methods used for the beneficial reuse of produced water, covering physical, chemical, and biological techniques, along with examples demonstrating their effectiveness in field case studies.